2005
DOI: 10.1158/0008-5472.can-05-0047
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Expression of BRAFV600E in Thyroid Cells of Transgenic Mice Results in Papillary Thyroid Cancers that Undergo Dedifferentiation

Abstract: The BRAF T1799A mutation is the most common genetic alteration in papillary thyroid carcinomas (PTC). It is also found in a subset of papillary microcarcinomas, consistent with a role in tumor initiation. PTCs with BRAF T1799A are often invasive and present at a more advanced stage. BRAF T1799A is found with high prevalence in tall-cell variant PTCs and in poorly differentiated and undifferentiated carcinomas arising from PTCs. To explore the role of BRAF V600E in thyroid cancer pathogenesis, we targeted its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
295
1
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(325 citation statements)
references
References 43 publications
(61 reference statements)
19
295
1
10
Order By: Relevance
“…In the study of Nikiforova et al (7), all BRAF-mutant poorly differentiated and anaplastic carcinomas contained areas of preexisting papillary carcinoma, and the BRAF V600E mutation was present in both the well-differentiated and dedifferentiated components, suggesting that it may have contributed to the transition from PTC to anaplastic carcinoma. In support of this hypothesis, thyroid-specific expression of BRAF V600E induces goiter and invasive PTC, which transitions to poorly differentiated carcinomas (14).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the study of Nikiforova et al (7), all BRAF-mutant poorly differentiated and anaplastic carcinomas contained areas of preexisting papillary carcinoma, and the BRAF V600E mutation was present in both the well-differentiated and dedifferentiated components, suggesting that it may have contributed to the transition from PTC to anaplastic carcinoma. In support of this hypothesis, thyroid-specific expression of BRAF V600E induces goiter and invasive PTC, which transitions to poorly differentiated carcinomas (14).…”
Section: Discussionmentioning
confidence: 82%
“…Mitsutake et al recently showed that BRaf is the key mediator of rearranged during transfection (RET)/papillary thyroid carcinoma (PTC) -induced extracellular signal-regulated kinase (ERK) phosphorylation in thyroid cells (13). Thyroid-specific expression of BRAF V600E induces goiter and invasive papillary carcinoma, which transitions to poorly differentiated carcinoma (14). The precise effect of BRAF mutations in the clinical aggressiveness of thyroid carcinomas, as well as its potential role as a therapeutic target, is still under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that these transgenic animals had PTCs and showed invasion, a common property of aggressive tumors [35]. All these data suggest that mutations in BRAF can be used as a novel marker for the prognosis of thyroid cancer.…”
Section: Brafmentioning
confidence: 77%
“…Other mutation involving in PTC is RAS mutation which occurs in 10-20% of tumors and this mutation in PTC almost always follicular variant in histology. Solid variant of PTC also has a different type of mutation which is associated with RET/PTC3 rearrangement (Knauf et al, 2005;Nikiforova and Nikiforov, 2009). Although BRAF mutation as a diagnostic test is specific for PTC, there are studies that stated its limitation as a diagnostic tool because of its low sensitivity (Xing, 2007;2009) There are some studies evaluated BRAF mutation diagnostic value.…”
Section: Discussionmentioning
confidence: 99%